Carlos L. Marcos, Ángel Allepuz Pedreño (eds.) Alberto Campo Baeza. El bisturí en la linea Alicante, Universitat de Alicante 2018 - Hugo Barros Costa (Diségno)
El Bisturí en la línea was presented as part of the XVII Congress of Architectural Graphic Expression, celebrated in July 2018 at the University of Alicante. This book was introduced as a complement to the drawings and models exhibition of Alberto Campo Baeza, Professor at the School of Architecture of Madrid